Saccharification of citrus wastes by immobilized polygalacturonase in an improved alginate matrix - Ramírez Tapias, Yuly Andrea (2017)
Enzyme immobilization using hydrogels is a low-cost and effective system for the degradation of bulk pectin derived from orange industry residues. Polygalacturonases obtained from four different bacterial strains of Streptomyces genus were immobilized in alginate gel and assayed for pectin hydrolysis. The enzyme from Streptomyces halstedii ATCC 10897 proved to be superior and more stable within the alginate matrix. Furthermore, a new strategy to improve alginate bead stability using a mixture of calcium and strontium is reported; this technique allowed enhancing the mechanical properties by combining different amounts of these cations for ionotropic gelation. The developed biocatalyst showed maximum hydrolysis at 2 h, generating 1.54 mg/mL of reducing sugars and decreasing the viscosity of polygalacturonic acid by 98.9%. Reusability up to 29 successive reactions (58 h) demonstrated a very stable performance. The heterogeneous biocatalyst was used in the enzymatic saccharification of orange peel albedo (2.23 mg/mL) for adding value to this agro-waste by industrial exploitation.